2010
DOI: 10.1007/s11357-010-9199-8
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial antioxidant effect of the Mediterranean diet supplemented with coenzyme Q10 in elderly men and women

Abstract: Postprandial oxidative stress is characterized by an increased susceptibility of the organism towards oxidative damage after consumption of a meal rich in lipids and/or carbohydrates. We have investigated whether the quality of dietary fat alters postprandial cellular oxidative stress and whether the supplementation with coenzyme Q(10) (CoQ) lowers postprandial oxidative stress in an elderly population. In this randomized crossover study, 20 participants were assigned to receive three isocaloric diets for peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…In the same population of this study, we previously demonstrated that the Med diet improves the postprandial oxidative stress with a higher increase in capillary flow and plasma nitric oxide levels, a lower plasma lipid peroxidation products, nitrotyrosine and protein carbonyl levels, lower plasma antioxidant enzyme activities (GPx, catalase (CAT) and SOD), (Yubero-Serrano et al 2010) and lower DNA damage in PBMCs (Gutierrez-Mariscal et al 2011). Addition of exogenous CoQ in synergy with a Med diet had an additive effect reducing the postprandial oxidative stress in elderly men and women.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In the same population of this study, we previously demonstrated that the Med diet improves the postprandial oxidative stress with a higher increase in capillary flow and plasma nitric oxide levels, a lower plasma lipid peroxidation products, nitrotyrosine and protein carbonyl levels, lower plasma antioxidant enzyme activities (GPx, catalase (CAT) and SOD), (Yubero-Serrano et al 2010) and lower DNA damage in PBMCs (Gutierrez-Mariscal et al 2011). Addition of exogenous CoQ in synergy with a Med diet had an additive effect reducing the postprandial oxidative stress in elderly men and women.…”
Section: Discussionmentioning
confidence: 52%
“…In line with this notion, oxidative stress has received considerable attention over the past several years in the fasting state; however, there is a paucity of data on postprandial oxidative stress. With regard to the postprandial state, we have recently demonstrated the antioxidant effect of Med diet rich in olive oil and that exogenous coenzyme Q 10 (CoQ: 2,3-dimethoxy-5-methy-6-decaprenyl-1,4-benzoquinone) supplementation in synergy with a Med diet (Med+CoQ diet) improves the postprandial oxidative stress in elderly men and women, with a higher increase in capillary flow, a lower plasma biomarker of oxidative stress levels and a greater postprandial decrease in plasma antioxidant enzymatic activities with respect to a Western diet rich in saturated fatty acid (SFA diet;Yubero-Serrano et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the same population of this study, we previously demonstrated the effect of Med+CoQ diet improves the postprandial oxidative stress (Yubero-Serrano et al 2010). However, few studies explored the effects that diet has on DNA damage during the postprandial state, or the effect of CoQ supplements in humans.…”
Section: Discussionmentioning
confidence: 58%
“…In fact, these studies have shown the existence of the relationship between dietary fat intake, aging, and oxidative stress (Sun et al 2012;Yubero-Serrano et al 2011;Ochoa et al 2003). Additionally, it has been demonstrated in animal models that the use of antioxidants as dietary supplements increases their lifespan (Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%